Development trajectories of river basins: a conceptual framework - Molle, Francois (International Water Management Institute, 2003)
The development of societies is shaped to a large extent by their resources base, notably water resources. Access to and control of water depend primarily on the available technology and engineering feats, such as river-diversion structures, canals, dams and dikes. As growing human pressure on water resources brings actual water use closer to potential ceilings, supply-augmentation options get scarcer, and societies, therefore, usually respond by adopting conservation measures and by reallocating water towards more beneficial uses.